Oil swellable polymer modified cement paste: Expansion and crack healing upon oil absorption. (1st July 2016) - Lu, Zichen; Kong, Xiangming; Yang, Ruifang; Zhang, Yanrong; Jiang, Lingfei; Wang, Ziming; Wang, Qichun; Liu, Wei; Zeng, Min; Zhou, Shiming; Dong, Biqin; Xing, Feng
Highlights: An oil swellable polymer (OSP) with oil absorptivity as high as 700% is synthesized. Addition of OSP decreases the total porosity of the hardened cement paste (HCP). Addition of OSP reduces the water adsorption rate and increases the oil absorptivity of HCP. Incorporation of OSP significantly increases the expandability of HCP upon oil absorption. A novel technique to achieve a crack self-healing property is developed. Abstract: This paper proposes a novel approach to achieve self-healing property of cement sheath in the oil well triggered by oil leakage through cracks. An oil swellable polymer (OSP) with oil absorptivity as high as 700% was synthesized through emulsion polymerization. The OSP dispersion was added into the Portland cement paste. It is found that the oil absorption and the linear expansion of the OSP modified hardened cement paste (MHCP) are greatly increased compared to the blank hardened cement paste (BHCP). Pore structure measurements by N2 adsorption show that the addition of OSP decreases the total porosity of MHCP which confirms that the formation of the polymeric film in MHCP. The self-healing ability of MHCP was evaluated by the oil flow test through a single crack in the cylindrical specimen. The oil flow tests indicate that the leakage of oil through the crack is gradually mitigated due to the expansion of the MHCP and thus the self-healing ability is successfully achieved.